Designing for scale: optimising the health information system architecture for mobile maternal health messaging in South Africa (MomConnect). (24th April 2018) - Seebregts, Christopher; Dane, Pierre; Parsons, Annie Neo; Fogwill, Thomas; Rogers, Debbie; Bekker, Marcha; Shaw, Vincent; Barron, Peter
Abstract : MomConnect is a national initiative coordinated by the South African National Department of Health that sends text-based mobile phone messages free of charge to pregnant women who voluntarily register at any public healthcare facility in South Africa. We describe the system design and architecture of the MomConnect technical platform, planned as a nationally scalable and extensible initiative. It uses a health information exchange that can connect any standards-compliant electronic front-end application to any standards-compliant electronic back-end database. The implementation of the MomConnect technical platform, in turn, is a national reference application for electronic interoperability in line with the South African National Health Normative Standards Framework. The use of open content and messaging standards enables the architecture to include any application adhering to the selected standards. Its national implementation at scale demonstrates both the use of this technology and a key objective of global health information systems, which is to achieve implementation scale. The system's limited clinical information, initially, allowed the architecture to focus on the base standards and profiles for interoperability in a resource-constrained environment with limited connectivity and infrastructural capacity. Maintenance of the system requires mobilisation of national resources. Future work aims to use the standard interfaces to include data from additional applications as well as to extend and interface the framework with other public health information systems in South Africa. The development of this platform has also shown the benefits of interoperability at both an organisational and technical level in South Africa.